310 nm UV-LEDs attenuate imiquimod-induced psoriasis-like skin lesions in C57BL/6 mice and inhibit IL-22-induced STAT3 expression in HaCaT cells. Issue 8 (25th June 2020) - Kwon, Tae-Rin; Lee, Sung-Eun; Kim, Jong Hwan; Na Jang, You; Kim, Su-Young; Mun, Seok Kyun; Kim, Chan Woong; Na, Jungtae; Kim, Beom Joon
Abstract : Ultraviolet light-emitting diodes (UV-LEDs) are a novel light source for phototherapy. Abstract : Ultraviolet light-emitting diodes (UV-LEDs) are a novel light source for phototherapy. This study aimed to evaluate the therapeutic effects of UV-LEDs on psoriasis. Importantly, 310 nm UV-LEDs have not been studied in psoriasis in vitro and in vivo . Effects due to 310 nm UV-LED and 311 nm narrowband ultraviolet B (NBUVB) irradiation were compared for suppressing IL-22-induced activation of STAT3 expression using cell viability assay, western blotting, and immunocytochemistry. C57BL/6 mice were topically treated with imiquimod (IMQ) for 6 consecutive days and degenerative changes were observed. Test groups were irradiated with a 310 nm UV-LED and 311 nm NBUVB. Phenotypic observations, histopathological examinations, and ELISA were conducted with skin and blood samples. STAT3-dependent IL-22 signalling and effects in keratinocytes are negatively regulated by the 310 nm UV-LED, which significantly ameliorated IMQ-induced psoriasis-like dermatitis development and reduced Th17 cytokine levels (IL-17A, IL-22) in serum and dorsal skin. Histopathological findings showed decreases in epidermal thickness and inflammatory T-cell infiltration in the UV-LED-irradiated groups. Quantitative PCR confirmed a UV radiation energy-dependent decrease in IL-17A and IL-22 mRNA levels. The results demonstrated that UV-LEDs had anti-inflammatory and immunoregulatory effects. So, UV-LED phototherapy inhibits psoriasis development by suppressing STAT3 protein and inflammatory cytokines and could be useful in treating psoriasis.